2018
DOI: 10.15580/gjms.2018.1.010818003
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Fistulae Experience in a University Teaching Hospital: A South-South Nigeria Perspective

Abstract: Background: Genitourinary fistula is a debilitating condition affecting women globally with high incidences in developing countries. It remains an indicator of the quality of health care delivery women are offered.Objective: To present the experiences of genitourinary fistulas (GUF) at the University of Port Harcourt Teaching Hospital (UPTH), Rivers State. Methods:From January 2002 to December 2012, 104 consecutive patients with genitourinary fistulas were admitted for evaluation, treatment (surgical) and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…The finding of majority (69.2%) of the genitourinary fistulas in this study being of obstetric origin is in consonance with the finding in studies conducted in Nigeria [17][18][19] and other sub-Saharan African countries 12,21,22 and it exposes the failure of the health systems in the countries across the continent to deliver accessible, timely and appropriate intrapartum care to pregnant women.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding of majority (69.2%) of the genitourinary fistulas in this study being of obstetric origin is in consonance with the finding in studies conducted in Nigeria [17][18][19] and other sub-Saharan African countries 12,21,22 and it exposes the failure of the health systems in the countries across the continent to deliver accessible, timely and appropriate intrapartum care to pregnant women.…”
Section: Discussionsupporting
confidence: 89%
“…This is quite low and may not contribute significantly in clearing the backlog of patients living with fistula in the area. Similar to the finding in this study, only a few patients were also treated at the teaching hospitals across Nigeria, including University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria, 17 where only 67 patients were managed for genital tract fistula over a 10-year period; Obafemi Awolowo University Teaching Hospital, Ile-Ife, Nigeria, 18 where only 55 patients were managed over a 10-year period; and University of Ilorin Teaching Hospital, Ilorin, Nigeria, 19 where only 34 patients were managed over a 10-year period. The low patient turnout for management of fistula in this study and in studies conducted in the other teaching hospitals in Nigeria could be due to the high cost of admission and surgery in the tertiary hospitals in the country, thus making their services financially inaccessible to the fistula patients who are mostly poor.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Studies done in Kano [45], Jos [46] and Port Harcourt [47] have shown the relevance of marriage and ethnicity in the occurrence of Obstetric fistula. In this study, half of the respondents were married in a monogamous setting before fistula developed, a third married in a polygamous setting and just a few of the patients were single.…”
Section: Discussionmentioning
confidence: 99%
“…This in contrast to finding done in western Uganda 10 where 77.9% had successful closure of their fistula. This difference could be due to patient factors like size of fistula, comorbidities; surgeons' factors like skill, surgical technique, facilities, postoperative management and other variables which are difficult to compare [47]. Overall success rates of vesicovaginal fistula repair were 75% 91.5%, 92%, and 87.9% in Port Harcourt [47], Ile-Ife [51], Jos [46] and Ilorin [52], respectively.…”
Section: Discussionmentioning
confidence: 99%